Easing the transition of first year undergraduates through an immersive induction module. Issue 7 (3rd October 2017) - Turner, Rebecca; Morrison, David; Cotton, Debby; Child, Samantha; Stevens, Sebastian; Nash, Patricia; Kneale, Pauline
ABSTRACT: Entry into higher education (HE) is recognised as a challenging time for undergraduates as they negotiate the norms and practices of new academic communities and foster relationships with peers and academics. Given the significance of this time period, our University has piloted a new four-week module that immerses students in their discipline and provides them with the academic skills and networks to support them through this period and beyond. Here we report a comprehensive evaluation examining academic and student experience of this immersive module. We explore its impact on essential aspects of the transition experience e.g. social integration, academic literacies and the sense of preparation for HE. Whilst this new approach did have positive impacts on students' sense of integration, questions were raised around the extent to which it matched or even raised expectations, and the extent to which this prepared students for the rest of their studies.